CX-072 (pacmilimab), a Probody® PD-L1 inhibitor, in advanced or recurrent solid tumors (PROCLAIM-CX-072): an open-label dose-finding and first-in-human study. Issue 7 (23rd July 2021) - Naing, Aung; Thistlethwaite, Fiona; De Vries, Elisabeth G.E.; Eskens, Ferry A.L.M.; Uboha, Nataliya; Ott, Patrick A.; LoRusso, Patricia; Garcia-Corbacho, Javier; Boni, Valentina; Bendell, Johanna; Autio, Karen A.; Randhawa, Manreet; et al.
Abstract : Background: Probody ® therapeutics are antibody prodrugs that are activated in the tumor microenvironment by tumor-associated proteases, thereby restricting the activity to the tumor microenvironment and minimizing 'off-tumor' toxicity. We report dose-escalation and single-agent expansion phase data from the first-in-human study of CX-072 (pacmilimab), a Probody checkpoint inhibitor directed against programmed death-ligand 1 (PD-L1). Methods: In the dose-escalation phase of this multicenter, open-label study (NCT03013491 ), adults with advanced solid tumors (naive to programmed-death-1/PD-L1 or cytotoxic T-lymphocyte-associated antigen 4 inhibitors) were enrolled into one of seven dose-escalation cohorts, with pacmilimab administered intravenously every 14 days. The primary endpoints were safety and determination of the maximum tolerated dose (MTD). In the expansion phase, patients with one of six prespecified malignancies (triple-negative breast cancer [TNBC]; anal squamous cell carcinoma [aSCC]; cutaneous SCC [cSCC]; undifferentiated pleomorphic sarcoma [UPS]; small bowel adenocarcinoma [SBA]; and thymic epithelial tumor [TET]); or high tumor mutational burden (hTMB) tumors were enrolled. The primary endpoint was objective response (Response Evaluation Criteria In Solid Tumors v.1.1). Results: An MTD was not reached with doses up to 30 mg/kg. A recommended phase 2 dose (RP2D) of 10 mg/kg was chosen based on pharmacokinetic and pharmacodynamic findings in the expansion phase. Ninety-eight patients enrolled in the expansion phase: TNBC (n=14), aSCC (n=14), cSCC (n=14), UPS (n=20), SBA (n=14), TET (n=8), and hTMB tumors (n=14). Of 114 patients receiving pacmilimab at the RP2D, grade ≥3 treatment-related adverse events (TRAEs) were reported in 10 patients (9%), serious TRAEs in six patients (5%), and treatment discontinuation due to TRAEs in two patients (2%). Grade ≥3 immune-related AEs occurred in two patients (rash, myocarditis). High PD-L1 expression (ie, >50% Tumor Proportion Score) was observed in 22/144 (19%) patients. Confirmed objective responses were observed in patients with cSCC (n=5, including one complete response), hTMB (n=4, including one complete response), aSCC (n=2), TNBC (n=1), UPS (n=1), and anaplastic thyroid cancer (n=1). Conclusions: Pacmilimab can be administered safely at the RP2D of 10 mg/kg every 14 days. At this dose, pacmilimab had a low rate of immune-mediated toxicity and showed signs of antitumor activity in patients not selected for high PD-L1 expression. Trial registration number: NCT03013491 .